Assessing disruption of longitudinal connectivity on macroinvertebrate assemblages in a semiarid lowland river - Leiva, Marta Elisabeth (2017)
Aim: Our aim in this study was evaluate the effects of flow regulation for irrigation on the macroinvertebrate assemblages in a semiarid river. Methods:We sampled two reaches in Dulce River; one placed upstream a weir that diverts flow into a network of irrigation channels and the other downstream that weir, in the assessment of the fluvial discontinuity. We assess the differences among reaches and sites, environmental variables, invertebrate density, richness and Shannon-Wiener index applying non-parametric analyses of variance Kruskal Wallis. The similarity percentage analysis (SIMPER) was used to identify which species contributed to the dissimilarities on macroinvertebrate assemblage structure. Canonical Correspondence Analysis (CCA) was performed with the total set of samples to explore macroinvertebrate distribution in reaches and associations of the assemblages with habitat variables. Results .The density, richness and Shannon index values did not show differences between the reaches located upstream and downstream. Beta diversity (Whittaker) was 0.72 among upstream sites, 0.56 among downstream sites and higher species turnover (0.73) was obtained between both reaches. The Canonical Correspondence Analysis explained 46.71% of the variance differentiating upstream sites explained by higher values of organic matter of bottom sediments and discharge, high density of Nais communis, Bothrioneurum americanum, Pelomus, Stephensoniana trivandrana, Pristina menoni, P. jenkinae, P.longidentata, P. americana, Dero obtusa, Endotribelos, Heleobia and Turbellaria. The downstream sites were associated to coarser substratum and higher density of Lopescladius, Polypedilum, Cricotopus, Thienamaniella, Cryptochironomus, Baetidae, Nematoda and Corbicula fluminea. Conclusions: The low-flow disturbance had effects on the composition of the benthic invertebrate assemblages, but attributes (such as density and richness) showed a lower variability probably because of taxa replacement.